Pseudomonas aeruginosa Takes a Multi-Target Approach to Achieve Junction Breach - Golovkine, Guillaume; Reboud, Emeline; Huber, Philippe (Frontiers in Cellular and Infection Microbiology, 2018)
P. aeruginosa is an opportunistic pathogen which uses a number of strategies to cross epithelial and endothelial barriers at cell-cell junctions. In this review, we describe how the coordinated actions of P. aeruginosa’s virulence factors trigger various molecular mechanisms to disarm the junctional gate responsible for tissue integrity.